Factors associated with false-positive fecal immunochemical tests in a large German colorectal cancer screening study - Amitay, Efrat L.; Cuk, Katarina; Brenner, Hermann (International journal of cancer, 2019)
In recent years fecal immunochemical tests (FITs) have been offered as a primary screening test for colorectal cancer (CRC) in a growing number of countries. Our study aims to identify factors associated with apparently false-positive results of FITs. In this cross-sectional study within the German population-based screening colonoscopy program, participants were invited to provide a stool sample for FIT prior to colonoscopy. Four thousand six hundred and fifty six participants aged 50-79 years with no known history of CRC or inflammatory bowel disease (IBD) and no findings of neoplasms at screening colonoscopy were included in the current analyses. Main outcome measures were rates and factors associated with apparently false-positive FIT results. Apparently false-positive FIT results were found for 378 participants (8.1%). Male sex (OR = 1.30, 95%CI 1.03, 1.62), age ≥65 years (OR = 1.27, 95%CI 1.01, 1.59), a BMI ≥30 kg/m2 (OR = 1.81, 95%CI 1.36, 2.40), current smoking (OR = 1.63, 95%CI 1.18, 2.25), use of aspirin (OR = 1.36, 95%CI 1.02, 1.82) and a new diagnosis of IBD (OR = 9.13, 95%CI 2.18, 38.19) or other non-neoplastic findings (OR = 1.86, 95%CI 1.37, 2.51) at screening colonoscopy were independently associated with significantly increased odds of a positive FIT. Although considered false positive in the context of CRC screening, the identified factors associated with apparently false-positive FIT results are known risk factors for and may point to conditions other than colorectal neoplasms that may be potential sources of gastrointestinal bleeding, potentially requiring further medical follow up.
Gesehen am 08.04.2019
First published: 09 November 2018